Premarital Sexual Behavior, Sexual Assertiveness, and Sex Guilt Among College Students - Anikmah Al Mutoharoh; Nani Nuranisah Djamal; Tahrir Tahrir (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
The phenomenon of premarital sexual behavior in college students is a moral problem demanding serious attention. A key determinant in reducing this behavior is the interplay between sexual assertiveness and sex guilt. Therefore, this study aims to determine the effect of sexual assertiveness and sex guilt on premarital sexual behavior. A quantitative approach is used with multiple linear regression analysis techniques. The participant consists of 153 students residing in Bandung City, aged 18-24 years, who are presently or have been in a relationship and are unmarried. The results show that sexual assertiveness and sex guilt have negative significant effect on premarital sexual behavior both simultaneously and partially with contribution of 35.9%. In conclusion, these variables are crucial for students as they can prevent them from engaging in premarital sexual behavior ranging from mild to severe risks.